Enhancing glucose flux into sweat by increasing paracellular permeability of the sweat gland. - Andrew Jajack; Michael Brothers; Gerald Kasting; Jason Heikenfeld (PLoS ONE)
Non-invasive wearable biosensors provide real-time, continuous, and actionable health information. However, difficulties detecting diluted biomarkers in excreted biofluids limit practical applications. Most biomarkers of interest are transported paracellularly into excreted biofluids from biomarker-rich blood and interstitial fluid during normal modulation of cellular tight junctions. Calcium chelators are reversible tight junction modulators that have been shown to increase absorption across the intestinal epithelium. However, calcium chelators have not yet been shown to improve the extraction of biomarkers. Here we show that for glucose, a paracellularly transported biomarker, the flux into sweat can be increased by >10x using citrate, a calcium chelator, in combination with electroosmosis. Our results demonstrate a method of increasing glucose flux through the sweat gland epithelium, thereby increasing the concentration in sweat. Future work should examine if this method enhances flux for other paracellularly transported biomarkers to make it possible to detect more biomarkers with currently available biosensors.